The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1103/physrevb.15.3652
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of adsorbed layers of nitrogen, oxygen, and sulfur on copper (100)

Abstract: Adsorbed layers of nitrogen and oxygen in the c(2 X 2) structure and sulfur in the (2 X 2) structure on copper (100) have been studied. Ultraviolet photoemission spectroscopy (UPS) shows that each of these layers induces a resonance above the "d band" of copper at about 1.3-eV binding energy with respect to the Fermi level and below the "1 band" at about 6-eV binding energy. X-ray photoemission spectroscopy has been used to determine that the 1s electronic binding energies of adsorbed atoms of c(2 X 2) nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…yields the N Auger peak indicated. Analysis of the fine structure of the adsorbate peaks showed good agreement with those obtained by Tibbetts et al (5). Assuming the peak-peak heights are proportional to elemental concentration, taking into account the linear energy dependence of the sensitivity of the CMA and the Auger yields of the elements (8), it is found that the elemental concentrations for 0, N and S are in the ratio 1:.73:.77.…”
Section: Surface Characterizationsupporting
confidence: 72%
“…yields the N Auger peak indicated. Analysis of the fine structure of the adsorbate peaks showed good agreement with those obtained by Tibbetts et al (5). Assuming the peak-peak heights are proportional to elemental concentration, taking into account the linear energy dependence of the sensitivity of the CMA and the Auger yields of the elements (8), it is found that the elemental concentrations for 0, N and S are in the ratio 1:.73:.77.…”
Section: Surface Characterizationsupporting
confidence: 72%
“…The surface energies, work functions and interlayer relaxations for slabs of 3, 5, 7, and 9 layers of copper are compared in Table II 27 . A further requirement of the thickness of the slab is that the interaction of the Co layers on both sides of the slab trough the substrate is negligible for the questions of concern.…”
Section: Calculational Detailsmentioning
confidence: 99%
“…Concerning the specific interaction of H 2 S with Ag͑111͒, almost all previous studies have focused on using H 2 S as a source of adsorbed S. In those studies, dissociative adsorption was achieved using high pressure and/or elevated surface temperature when H 2 S was in the gas phase, [1][2][3][4][5][6][7] or using electrochemical methods when H 2 S was in liquid solution. 7,8 In contrast, the present paper deals with the state of the molecule that is obtained by adsorption at low pressure and at temperatures ͑T͒ of 5-30 K.…”
Section: Introductionmentioning
confidence: 99%